Emerging advancements for virtual and augmented reality in healthcare - Reis, Sara; Queiros, Ricardo; Coelho, Luis (IGI Global, 2022)
"The goal of this book is to show how to put Virtual Reality in action by linking academic and informatics researchers with professionals who use and need VR in their day-a-day work, with a special focus on healthcare professionals and related areas for the purpose of exchanging the knowledge, information and technology from the international communities in the area of VR, AR and XR.
Includes bibliographical references and index
Section 1. Preventive healthcare and awareness. Chapter 1. Virtual reality in healthcare: a survey ; Chapter 2. Virtual and augmented reality awareness tools for universal design: towards active preventive healthcare -- Section 2. Education and training. Chapter 3. Educational technology based on virtual and augmented reality for students with learning disabilities: specific projects and applications ; Chapter 4. A pedagogical paradigm shift: prospective epistemologies of extended reality in health professions education ; Chapter 5. Virtual simulation: a flipped classroom teaching tool for healthcare education ; Chapter 6. Building an extended reality pedagogical continuum through 180 first-person point-of-view video: from VR to computer and mobile displays to AR -- Section 3. Physical intervention. Chapter 7. Application of virtual/augmented reality in surgical procedures: bibliographical review in recent developments ; Chapter 8. Improvements of virtual and augmented reality for advanced treatments in urology ; Chapter 9. Emerging advancement for augmented reality (AR) and virtual reality (VR) in dentistry -- Section 4. Mental intervention. Chapter 10. Virtual reality exposure therapy and physiological data analysis for treatment of stress disorders ; Chapter 11. Evidence-based virtual reality use for mental health conditions ; Chapter 12. Evidence-based immersive technology use in cognitive assessments and cognition-based interventions -- Section 5. Trends. Chapter 13. Application of virtual reality in cognitive rehabilitation: a road ahead ; Chapter 14. The future of virtual reality and deep learning in visual field testing. - Mode of access: World Wide Web
Keywords: Virtual reality; Augmented reality; Therapeutics; Gesundheitswesen; Erweiterte Realität -- Informatik; Medizinische Ausbildung; Virtuelle Realität; Medizintechnik; Therapie; Aufsatzsammlung